Dark Energy and Dark Matter - Regmi, Jeevan (Himalayan Physics, 2013)
The new discoveries and evidences in the field of astrophysics have explored new area of discussion each day. It provides an inspiration for the search of new laws and symmetries in nature. One of the interesting issues of the decade is the accelerating universe. Though much is known about universe, still a lot of mysteries are present about it. The new concepts of dark energy and dark matter are being explained to answer the mysterious facts. However it unfolds the rays of hope for solving the various properties and dimensions of space. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 90-94 Uploaded date: 12/23/2013